The effect of surface temperature on optical properties of molybdenum mirrors in the visible and near-infrared domains. (4th July 2018) - Minissale, Marco; Zeweldi, Gebrehiwot Tesfay; Bisson, Régis; Gallais, Laurent
Abstract: Molybdenum mirrors will be used in several optical diagnostics to control the plasma in the ITER tokamak. In this harsh environment, mirrors can undergo transient temperature rises. Thus, the knowledge of the temperature dependence of optical properties of molybdenum is necessary for a good operation of optical systems in ITER. Molybdenum optical properties have been extensively studied at room temperature, but little has been done at high temperatures in the visible and near-infrared domains. We investigate the temperature dependence of molybdenum reflectivity from the ambient to high temperatures (<800 K) in the 500–1050 nm spectral range. Experimental measurements of reflectivity, performed via a spectroscopic system coupled with laser remote heating, show a maximum increase of 2.5% at 800 K in the 850–900 nm wavelength range and a non-linear temperature dependency as a function of wavelength. We describe these dependencies through a Fresnel and a Lorentz–Drude model. The Fresnel model accurately reproduces the experimental curve at a given temperature by using a parabolic temperature dependency for the refractive index, n, and a linear dependency for the extinction coefficient, k . We develop a Lorentz–Drude model to describe the interaction of light with charge carriers in the solid. This model includes temperature dependency on both intraband (Drude) and interband (Lorentz) transitions. It is able to reproduce the experimental results quantitatively, highlighting a non-trivial dependency of interband transitions on temperature. Eventually, we use the Lorentz–Drude model to evaluate the total emissivity of molybdenum from 300 K to 2800 K, and we compare our experimental and theoretical findings with previous results.